An investigation into the popularity of Latin soap operas among Zambian viewers: a reception study of Lusaka women - Mushambatwa, Iñutu (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2017)
This study explores the way Zambian women make sense of the representations and discourses in the Latin soaps that they watch daily. The study seeks to find out what pleasures and values Zambian women get from these soaps given that the Latin and Zambian cultures are very different. This is in the context of Zambia being a socially conservative patriarchal and Christian nation, where the legal and traditional practices focus on the authority of the man in relationships, particularly in marriages. The lens through which this study is conducted is provided by the media imperialism thesis and its critiques. The study explores the underlying proposition of the thesis that global media are uncritically received by people in the Third World which contributes to global cultural homogenisation. Drawing on ethnographic critiques of this position, my study provides a close examination of actual viewers in actual contexts in order to understand the complex relationships that often exist between global media and local audiences. Using qualitative methods rooted in reception analysis, the study explores the pleasures women get from these soap operas and in particular, the symbolic means that these soaps provide for what has been referred to as 'symbolic distancing'. Symbolic distancing foregrounds the way local audiences use global media to distance themselves from the cultural confines of their local environments, exposing them to other worldviews and understandings from which they can critique their own lived conditions of existence. In line with this, the study evaluates whether the viewers' perceptions and values have been changed by the viewing of these Latin soaps.
Keywords: Uncatalogued